Implementasi Sistem IoT untuk Monitoring Konsumsi Energi Listrik di Rumah Pintar - Yusuf, Muhamad Burhanudin; Rosyidi, Lukman; Saptono, Henry (LPPM STT Terpadu Nurul Fikri, 2025)
Technological advancements have transformed household electricity usage, increasing dependence on electronic devices and demanding efficient solutions to monitor energy consumption. Law Number 30 of 2009 encourages energy efficiency. This research aims to develop and test a household electricity consumption monitoring system based on the Internet of Things (IoT) using ACS712 current sensors and the NodeMCU ESP8266 microcontroller. This study designs and implements a household electricity consumption monitoring system using ACS712 sensors, employing research and development (R&D) methods. The results show that the system successfully implements ACS712 sensors with high accuracy, enabling efficient monitoring through the Pemantauan.com monitoring platform. Real-time data provides detailed daily energy consumption patterns, optimising energy use by reducing waste. Testing results indicate that this system achieves a 100% success rate in measuring electrical loads and transmitting data, demonstrating high accuracy and reliability in monitoring electricity consumption. To further enhance the system's effectiveness, it is recommended that it be integrated with an alarm or notification system that provides real-time alerts to users in the event of anomalies or unusual increases in electricity consumption. This will help users to take immediate actions necessary to save energy and avoid unwanted electricity costs.